Ebe ve Hemşireler için Fizik Muayene - Çobadak Çalt, Aysun; Kaşıkçı, Esengül; Aydın Sayılan, Aylin; Kurt, Duygu; Kınıcı Dirik, Ezgi; Paslı Gürdoğan, Eylem; Aksoy, Berna; Barış Eren, Nadiye; Soydaş, Duygu; Kızılcık Özkan, Zeynep; Tandoğan, Özden; Pelin, Meryem; et al. (2023)
-